Joe [videorecording (DVD)] - Cage, Nicolas, 1965-; Sheridan, Tye, 1996-; Brown, Larry, 1951-2004 (Lionsgate, 2014)
A hard-living ex-con is the unlikeliest of role models, but when he meets a troubled fifteen-year-old homeless boy in need of help from a violent and destitute father, Joe is faced with the heartbreaking choice of redemption or ruin.